Deconstructing the Symbiosis of Power, Crime, and Law: A Study of Online Gambling in Indonesia through Routine Activities and Critical Legal Theory - Idris, Maulana Fahmi; Amalia Sari, Farida; Riskia Putri, Nurlila; Diva Wulandari, Yesi (Universitas Sains dan Teknologi Komputer, 2025)
The phenomenon of online gambling in Indonesia has experienced a significant escalation in recent years, marked by an increase in the money turnover reaching Rp 600 trillion by 2024 and a rise in the number of active players reaching 11 million people. Ironically, this practice has thrived despite being legally prohibited by Law No. 7 of 1974 and the ITE Law. This research aims to analyze the legal and political dynamics in addressing online gambling in Indonesia by combining two theoretical frameworks: Routine Activities Theory to examine the structure of opportunities for digital crime, and Critical Legal Theory to trace the ambiguous power relations and regulations. The approach used is qualitative with an instrumental case study design, which includes document analysis, in-depth interviews, and digital observation of the top five gambling sites. The research results show that surveillance gaps, hard-to-track financial technology, and the involvement of powerful actors strengthen the online gambling ecosystem. Not only are adults involved, but the victims now include children from elementary to middle school age. This practice has profound impacts on family economics, education, and mental health. This study concludes that weak law enforcement is not solely due to technical limitations, but also because of structural compromises within state institutions. This study contributes to the development of an integrative theoretical framework in understanding digital crime, as well as offering a more preventive and accountable policy direction in addressing online gambling in Indonesia.